Malaysian domestic debts economic growth - Dullie, Fadzyinie (2012)
Since its independence, the government has always been setting goals and implemented policies that intervene in the Malaysian economy. The Malaysian economy has a strong base on electronic components and electronic goods, on top of the abundance of natural resources such as timber, oil, palm oil, rubber and so on. However, it is arguable that, the economy needs government's intervention and policies to set its direction and as a result the federal government has long and always been spending on expenditures for public schemes, projects and programs to support the people and attract private investments especially foreign capital into the country to fuel growth in the economy. Therefore, these policies led to huge amounts of fiscal spending where the federal government today incurred large amounts of domestic debts to finance its budget deficits year on year. This study aims to investigate the effect of the federal government's level of domestic debts on economic growth in Malaysia. This involves estimating long-run and short-run coefficient looking at the relationship between gross domestic product with government domestic debt to GDP ratio, inflation and the federal government's budget deficits using the Autoregressive Distributed Lag (ARDL) approach. The period sample is from 1998 to 2010 using quarterly data. Through ARDL estimation, the long-run result shows that domestic debt to GDP ratio has a positive relationship with economic growth, while in the short-run result, domestic debt to GDP has a negative relationship with economic growth. However, inflation and budget deficit do not play any role in economic growth.